Completion of Matrix Inversions Using Elementary Matrix Inverse Multiplication Method - Cipta, Hendra (International Journal of Science, Technology & Management, 2020)
Abstract. Given a matrix A is ordo . Elementary matrix inverse multiplication produces inverse matrix A which is where I is an identity matrix and is an inverse matrix A. The problem discussed in this research is to find a solution the ordo of matrices by using inverse elementary matrix inversion method with the steps given in solving by completing the smallest ordo matrix first up until the ordo matrix . Keywords: Matrix, Inverse Matrix, Multiplication of Elementary Matrix.